Risk factors associated with COVID-19 during the pandemic in Puerto Vallarta, Mexico - Partida Perez, Miriam; Valencia De León, Alejandra del Rosario; Torres Jasso, Juan Heriberto (Horizonte Sanitario, 2025)
Objective: To analyze the risk factors associated with SARS-CoV-2 infection, as well as the dynamics of viral variants in the Puerto Vallarta region, Jalisco, during the COVID-19 pandemic. Materials and methods: A cross-sectional observational study was conducted to identify infection by SARS-CoV-2 and the variants present in infected individuals were carried out by Real-time Polymerase Chain Reaction between April 2020 and April 2022. Results: A total of 5,646 individuals were analyzed, of which 3,336 people obtained a negative result for SARS-CoV-2, while 2,310 tested positive. The presence of several SARS-CoV-2 variants was detected, with a predominance of the wild variant. Statistically significant associations were found between symptoms such as cough (p=0.000), fever (p=0.000), loss of smell (p=0.000) and taste (p=0.000), as well as with morbidities such as obesity (p=0.000) and diabetes (p=0.000) concerning SARS-CoV-2 infection. These conditions, reported more frequently in positive cases, highlight their relevance in clinical management. Additionally, the dynamics of virus variants during this period were investigated. Conclusions. SARS-CoV-2 detection contributed to identifying positive cases, a requirement for prevention strategies, while variant identification allowed contextualizing changes in local epidemiology. Keywords: COVID-19; RT-PCR; Comorbidities.